Do plano ao espaço, o uso da geometria para compreender o funcionamento do GPS - Brezinski, Camila Andreatta da Silva (2025)
In this dissertation we explore the basic concepts of Plane and Spatial Geometry that make it possible to understand how the Global Positioning System-GPS works. Furthermore, interdisciplinarity between the disciplines of Mathematics and Geography is also worked on. The GPS presence in smartphones helps to stimulate students’ curiosity as a starting point for Geometry learning. By making students reflect on how a cell phone can locate and be located, we open a path to show how basic content/knowledge is involved in the technology they appreciate so much. By showing that Geometry and Geography work together to make it possible to find a point on the Globe based on geographic coordinates, latitude and longitude, we hope that students will be able to understand concepts that previously seemed abstract and purposeless during classes. Encouraging the search for a connection between theoretical content and real life is a way for the school to remain relevant to the student who needs that “little push” to commit to their studies and learn effectively